Enhancing Electrocatalytic Production of H2O2 by Modulating Coordination Environment of Cobalt Center. (30th June 2021) - Wu, Guoling; Yang, Zhongjie; Zhang, Tianlin; Sun, Yali; Long, Chang; Song, Yaru; Lei, Shengbin; Tang, Zhiyong
Abstract : As an environmentally friendly oxidant, H2 O2 is widely utilized in various fields; however, its production methods remain limited to the chemical anthraquinone process. Alternatively, electrocatalytic oxygen reduction possesses numerous notable advantages (e.g., cost‐effectiveness, small‐scale, and distributed nature). As electrocatalytic oxygen reduction has been widely investigated in the fields of fuel cells and metal‐air batteries, the mechanism of the 2e − ‐ORR pathway for producing H2 O2 is not sufficiently clear. Herein, we explore the effect of the cobalt (Co) coordination environment on the electrochemical production of H2 O2 . The detailed investigation on N‐, P‐, and S‐coordinated Co catalysts (Co1 N1 N3, Co1 P1 N3, and Co1 S1 N3 ) demonstrates that changing the coordination environment evidently affects the H2 O2 selectivity, and the S‐coordinated Co exhibits the best catalytic performance. This finding would lead to the design and selection of catalysts at atomic level for producing H2 O2 via electrocatalytic oxygen reduction. Abstract : By rationally modulating the coordination environment of the metal active center, the performance of the ORR catalyst is effectively tuned. The electrochemical tests and the chemical quantification of H2 O2 demonstrate that Co1 S1 N3 possesses the best catalytic performance at 0.2 V, which is highly sensitive to the applied voltage.